Phase I study of highly selective inhibitor of VEGFR tyrosine kinase, tivozanib, in Japanese patients with solid tumors - Niwakawa, Masashi (Cancer Sci, 2013)
Tivozanib is a potent and selective inhibitor of vascular endothelial growth factor receptor (VEGFR) tyrosine kinases. A previous clinical trial in the EU and USA indicated that tivozanib at the maximum tolerated dose of 1.5 mg/day showed an antitumor activity in patients with renal cell carcinoma. This Japanese phase I study was designed to determine the recommended phase II dose of tivozanib for Japanese patients; secondary objectives included pharmacokinetic/pharmacodynamic profiles and preliminary efficacy. Daily treatment with tivozanib in a 3‐weeks‐on/1‐week‐off cycle was examined in nine Japanese patients with advanced solid tumors in the 3 + 3 design (Level 1, 1.0 mg; Level 2, 1.5 mg). No dose‐limiting toxicity was observed throughout the study, and the maximum tolerated dose was not reached. The most commonly observed drug‐related adverse events were diarrhea, dysphonia, rash, thyroid stimulating hormone increase, and with severity grade ≥3, hand‐foot skin reaction, hypertension, and proteinuria. Those adverse events were generally well‐manageable and mostly resolved within the tolerability evaluation period. Serum exposure to tivozanib resulted in t (1/2) of more than >60 h. Increase of plasma VEGF and decrease of plasma VEGFR‐1 and VEGFR‐2 were observed 1–3 weeks after tivozanib treatment. Although no complete or partial response was observed, long‐term stable disease continuing more than 170 days was observed in three renal cell carcinoma patients who had failed prior VEGFR inhibitors. In conclusion, 1.5 mg/day of tivozanib in a 3‐weeks‐on/1‐week‐off setting was tolerable in Japanese patients, and was recommended for further clinical trials in the Japanese population. Clinical trial Registration No: JapicCTI‐090854.